Extending poly-victimization theory: Differential effects of adolescents' experiences of victimization on substance use disorder diagnoses upon treatment entry. (March 2019) - Davis, Jordan P.; Dworkin, Emily R.; Helton, Jesse; Prindle, John; Patel, Sadiq; Dumas, Tara M.; Miller, Sara
Abstract: Background: Although victimization is a known contributor to the development of substance use disorders, no research has simultaneously examined how characteristics of victimization experienced over time, such as the type of abuse, the presence of poly-victimization, closeness to perpetrator(s), life threat or fear, and negative social reactions to disclosing victimization, cluster into profiles that predict substance use disorders. Objective: The aim of the current study is to assess how profiles of victimization and trauma characteristics are associated with substance use disorders and assess potential gender differences. Participants and Setting: Participants were 20, 092 adolescents entering substance use treatment. Methods: We used latent class and multi-group latent class analysis to extract classes of victimization and associated characteristics. Emergent classes were used to predicted substance use disorder status at treatment intake. Results: Five classes were extracted: poly-victimization + high harmful trauma characteristics, sexual abuse + negative social reaction and perceived life threat, emotional abuse + trusted perpetrator, physical abuse and low all . Similar classes were found for the multi-group model. In both the overall and female-specific models, the poly-victimization + high harmful trauma characteristics class was more severe than all other classes in terms of opioid use disorder, tobacco use disorder, and dual diagnosis. Other class differences were found across gender. Conclusions: Adolescents entering treatment can be distinguished by their profiles of victimization experiences and associated characteristics, and these profiles evidence different associations with substance use disorder diagnoses. Results point to a need for more nuanced assessment of victimization experiences and gender-specific interventions.